MOLECULAR DETECTION OF PATHOTYPE OF MAREK’S DISEASE VIRUS IN LAYERS CHICKEN IN IRAQ - Malek A. Qadoori; S. S. Hameed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Marek’s disease virus (MDV) infects chickens and is among the most common tumor in animals. The first MDV vaccinations that prevented cancer and reduced losses in the chicken industry were live-attenuated vaccines. Despite the fact that the current gold standard vaccination effectively guards against the disease, because of the Meq gene the virus is continuously mutating to become more virulent. the two vaccine generations previously given protection was able to be overcome by emerging field strains. In the present study collecting the tissue samples from infected, A standardized PCR was used. 132-bp tandem repeat region targeted for serotype-1 MD viruses. in Further, the oncogenes’ characterization. PCR and nucleotide sequencing were used to detect Meq gen and viral interleukin 8 (vIL-8) gen. Meq gene sequence analysis for different clinical cases from Iraq revealed 100 % homology with Indian strain, Japan strain, Turkish strain, Germany strain (very virulent). and with (very very virulent) Iranian strains showed 100% identity with the Iraq strain. With the use of more GenBank sequences, a phylogenetic analysis of oncogenes was carried out. Finally, based on nucleotide and phylogenetic analyses of the viruses, we get to the conclusion that MDV strains found in the current outbreaks in Iraq could be classified as virulent or very very virulent pathotypes.